Louis, Dauphin de France (1661-1711) - Engraving 02 - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Louis, Dauphin de France (1661-1711) - Engraving 02. Engraved portrait of Louis, Dauphin of France (1661-1711)
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons